Global Impact of COVID-19 on Stroke Care and IV Thrombolysis. (8th June 2021) - Nogueira, Raul G.; Qureshi, Muhammad M.; Abdalkader, Mohamad; Martins, Sheila Ouriques; Yamagami, Hiroshi; Qiu, Zhongming; Mansour, Ossama Yassin; Sathya, Anvitha; Czlonkowska, Anna; Tsivgoulis, Georgios; Aguiar de Sousa, Diana; Demeestere, Jelle; et al.
Abstract : Objective: To measure the global impact of COVID-19 pandemic on volumes of IV thrombolysis (IVT), IVT transfers, and stroke hospitalizations over 4 months at the height of the pandemic (March 1 to June 30, 2020) compared with 2 control 4-month periods. Methods: We conducted a cross-sectional, observational, retrospective study across 6 continents, 70 countries, and 457 stroke centers. Diagnoses were identified by their ICD-10 codes or classifications in stroke databases. Results: There were 91, 373 stroke admissions in the 4 months immediately before compared to 80, 894 admissions during the pandemic months, representing an 11.5% (95% confidence interval [CI] −11.7 to −11.3, p < 0.0001) decline. There were 13, 334 IVT therapies in the 4 months preceding compared to 11, 570 procedures during the pandemic, representing a 13.2% (95% CI −13.8 to −12.7, p < 0.0001) drop. Interfacility IVT transfers decreased from 1, 337 to 1, 178, or an 11.9% decrease (95% CI −13.7 to −10.3, p = 0.001). Recovery of stroke hospitalization volume (9.5%, 95% CI 9.2–9.8, p < 0.0001) was noted over the 2 later (May, June) vs the 2 earlier (March, April) pandemic months. There was a 1.48% stroke rate across 119, 967 COVID-19 hospitalizations. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection was noted in 3.3% (1, 722/52, 026) of all stroke admissions. Conclusions: The COVID-19 pandemic was associated with a global decline in the volume of stroke hospitalizations, IVT, and interfacility IVT transfers. Primary stroke centers and centers with higher COVID-19 inpatient volumes experienced steeper declines. Recovery of stroke hospitalization was noted in the later pandemic months.